2020
DOI: 10.3389/fphy.2020.00347
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Serial Interval of the Novel Coronavirus Disease (COVID-19): A Statistical Analysis Using the Public Data in Hong Kong From January 16 to February 15, 2020

Abstract: Background: The emerging virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused a large outbreak of novel coronavirus disease (COVID-19) since the end of 2019. As of February 15, there were 56 COVID-19 cases confirmed in Hong Kong since the first case with symptom onset on January 23, 2020. Methods: Based on the publicly available surveillance data in Hong Kong, we identified 21 transmission events as of February 15, 2020. An interval censored likelihood framework is adopted to fit thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…Early modeling studies of COVID-19 case data found that the generation interval of SARS-CoV-2 was shorter than the serial interval, indicating that the average time between 1 person being infected and that person infecting someone else was shorter than the average time between 1 person developing symptoms and the person they infected developing symptoms. [2][3][4][5] This finding meant that the epidemic was growing faster than would be expected if transmission were limited to the period of illness during which individuals were symptomatic. By the time a second generation of individuals was developing symptoms, a third generation was already being infected.…”
Section: Introductionmentioning
confidence: 99%
“…Early modeling studies of COVID-19 case data found that the generation interval of SARS-CoV-2 was shorter than the serial interval, indicating that the average time between 1 person being infected and that person infecting someone else was shorter than the average time between 1 person developing symptoms and the person they infected developing symptoms. [2][3][4][5] This finding meant that the epidemic was growing faster than would be expected if transmission were limited to the period of illness during which individuals were symptomatic. By the time a second generation of individuals was developing symptoms, a third generation was already being infected.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this work, we will perform a statistical analysis of GI and SI. Several papers have quantified the GI, SI, and IP of COVID-19 by employing statistical and mathematical modeling (3,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Please see Table 1 for their estimated values and sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…We use an incubation period of 5.2 days and assume that infections occur randomly during the infectious period [53]; for more details, see [53,64,94]. We allow for T C E ∈ [2.67, 4.00].…”
Section: Exposure Carrier and Infection Transitionmentioning
confidence: 99%